Building Learning Communities in Terms of Improving English Vocabulary through Korean Drama with English Subtitle - Lida Holida Mahmud; Tryana Tryana (Universitas Pamulang, 2020)
The research explored the issues of the English teaching method as a foreign language. The purpose of the study is to improve students’ vocabulary of English. It focused on teaching technique in English vocabulary by using Korean Drama with English sub-title. In particular, it focused on students' feelings and behavior in line with a student’s test result of whether or not the implementation of Korean Drama with English subtitles in English teaching is beneficial for students’ improvement of English vocabulary. The literature review highlighted the connection between teaching methods and building learning community. Since the meaning of building learning communities is broad, the research focused on the motivation in watching Korean drama, it was linked to build learning community in terms of improving English vocabulary. The method employed during the research phase of this project has been done to generate data through questionnaires, interviews, and tests. Since the aim of the research is to see the possibility of Korean Drama in improving students' vocabulary in English, it was important to produce qualitative elicited partly through the use of test results and open questions in questionnaires and interviews. This study employed 70 respondents from the first semester students of the English Department in Universitas Pamulang as samples of the population. From the data analyses, it was found that there are some aspects that should be improved in the project itself such as feedback, support in continuing professional development of lectures and monitoring and also evaluation. From the findings, the research suggests that developing teaching should be in line with a system for fostering teachers to follow up and assist their abilities to sustain professional development independently, might assist in improving student’s competency.